Models for the reverse engineering of Java/Swing applications - Saraiva, João Alexandre (2006)
Interest in design and development of graphical user interface (GUIs) is growing in the last few years. However, correctness of GUI's code is essential to the correct execution of the overall software. Models can help in the evaluation of interactive applications by allowing designers to concentrate on its more important aspects. This paper describes our approach to reverse engineering abstract GUI models-based directly from the Java/Swing legacy code.